Extracting and comparing the intricacies of metadiscourse of two written persuasive corpora - Chan, Swee Heng; Helen, Tan (University of the West Indies, 2010)
Previous studies (Wu 2007; Hyland, 2004; Hyland & Tse 2004; Intaraprawat & Steffensen 1995; Crismore et al 1993; Vande Kopple 1985) have established the use of Metadiscourse (MD) as an essential element in writing as it allows the writer to create a dialogic space with his readers. In recent years, attempts have been made to analyse MD through the use of text corpus with the help of computer technology especially when the corpus is large. In this investigation, data have been obtained through an electronic means to illustrate the use of MD in writing samples of a group of Malaysian undergraduates. In order to investigate the use of MD by these students, their writing was benched against an established standard, the open access BAWE corpus, available online. The MD features were analysed through the concordancing software, monoConc Pro 2.2, for this research. The paper demonstrates how the software manages the data to reveal patterns of use between writers of the two corpora. The paper concludes on initial insights obtained from the comparison to show the nature and manner of MD between standard proficient writing(extract from BAWE corpus) and evolving student writing at the tertiary level that would have implications for writing improvement in educational institutions.